SIFAT MEKANIS DAN TEGANGAN DASAR 13 JENIS KAYU KALIMANTAN TIMUR - S Karnasudirdja; B Ginoga; Nurwati Hajib (Pusat Penelitian dan Pengembangan Hasil Hutan, 1986)
The green ultimate stress values of 13 Indonesia timbers from East Kalimantan are presented in this paper using the _ASTM D 145 - 70 test method. The result indicates a high coefficient of variation (53%) for work to proportional limit (Gonystylus bancanus), while the lowest recorded is 5,5% for compression perpendicular to the grain (Shorea ovalis). An estimate _of the dry ultimate stress (table 2), green basic stress (table 3) and dry basic stress (table 4) are attempted using regression equations.